Examining emergency department inequities in Aotearoa New Zealand: Findings from a national retrospective observational study examining Indigenous emergency care outcomes. (14th October 2021) - Curtis, Elana; Paine, Sarah‐Jane; Jiang, Yannan; Jones, Peter; Tomash, Inia; Healey, Olivia; Reid, Papaarangi
Abstract : This retrospective observational study used a Kaupapa Māori framework to investigate ED admissions into 18/20 District Health Boards in Aotearoa New Zealand (2006–2012). Despite some ED process measures being positive for Māori, for example arrival to assessment time and access block, others showed no difference, for example self‐discharge. Despite this, Māori mortality and ED re‐presentation were higher than non‐Māori. Our findings reinforce the need to investigate health professional bias and institutional racism within an acute care context. Abstract: Objective: There is increasing evidence that EDs may not operate equitably for all patients, with Indigenous and minoritised ethnicity patients experiencing longer wait times for assessment, differential pain management and less evaluation and treatment of acute conditions. Methods: This retrospective observational study used a Kaupapa Māori framework to investigate ED admissions into 18/20 District Health Boards in Aotearoa New Zealand (2006–2012). Key pre‐admission variable was ethnicity (Māori:non‐Māori), and outcome variables included: ED self‐discharge; ED arrival to assessment time; hospital re‐admission within 72 h; ED re‐presentation within 72 h; ED length of stay; ward length of stay; access block and mortality (in ED or within 10 days of ED departure). Generalised linear regression models controlled for year of presentation, sex, age, deprivation, triage category and comorbidity. Results: Despite some ED process measures favouring Māori, for example arrival to assessment time (mean difference −2.14 min; 95% confidence interval [CI] −2.42 to −1.86) and access block (odds ratio [OR] 0.89, 95% CI 0.87–0.91), others showed no difference, for example self‐discharge (OR 0.98, 95% CI 0.97–1.00). Despite this, Māori mortality (OR 1.60, 95% CI 1.50–1.71) and ED re‐presentation (OR 1.11, 95% CI 1.09–1.12) were higher than non‐Māori. Conclusion: To our knowledge, this is the most comprehensive investigation of acute outcomes by ethnicity to date in New Zealand. We found ED mortality inequities that are unlikely to be explained by ED process measures or comorbidities. Our findings reinforce the need to investigate health professional bias and institutional racism within an acute care context.